A review of the genus Satonius Endrödy-Younga from China with description of seven new species (Coleoptera: Myxophaga: Torridincolidae) - Liang, Zu-Long; Jiang, Zhuo-Yin; Bergsten, Johannes; Jia, Feng-Long; Ge, Si-Qin (Zootaxa, 2024)
Species of the genus Satonius Endrödy-Younga from China are briefly reviewed. Seven new species are described: Satonius cheni sp. nov. from Guangdong, Satonius nigriventralis sp. nov. from Shaanxi, Satonius panghongae sp. nov. from Jiangxi, Hunan, Guangxi and Zhejiang, Satonius quzhouensis sp. nov. from Zhejiang and Anhui, Satonius xinhuiensis sp. nov. from Guangdong, Satonius zhangi sp. nov. from Hunan, and Satonius zhenhuai sp. nov. from Hubei. Species diagnoses of the new species are provided, along with images of the habitus and illustrations of the aedeagus and metatrochanters for all available Chinese species. Additionally, further faunistic data of known Chinese species is supplemented. A key to all known species of the genus is also included.